PHYTOCHEMICAL EVALUATION AND ANTIOXIDANT SCREENING STUDIES OF OCIMUM TENUIFLORUM LINN SEEDS - Sharma, Jyotsana; Khurana, Navneet; Sharma, Neha; Garg, Rakesh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: In the existing study, Ocimum tenuiflorum was assessed for its antioxidant activity. This activity was assessed using the 2,2-diphenyl-1- picrylhydrazyl (DPPH) method. The drug was identified and standardized on the basis of organoleptic, negligible characters and its quantitative physicochemical standards. Methods: Preliminary phytochemical screening was also carried out to examine out the presence of various phytoconstituents. It revealed the presence of alkaloids, phytosterols, resin, flavonoids, tannins, diterpenes, and protein in the seed extract. DPPH method was done used for evaluating the antioxidant activity. Results: It has been observed that different concentrations (100, 200, 300, 400, and 500 Î¼g/mL) used had shown 82.1%, 83.4%, 86.6%, 89.1%, and 93.2% of cell inhibition, respectively. Conclusion: Thus, the present study on pharmacognostic standardization, physicochemical evaluation and in vitro antioxidant activity of O. tenuiflorum seed would be useful to supplement information in regard to its in vivo evaluation for different pathological conditions.